(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
This paper explores some of the areas of convergence between Tao and Heidegger’s thought. More specifically, the analysis touches upon the different manners in which the concepts of totality and interdependence, and being and nothing are encountered in Tao and Heidegger’s work and how they are reflected in therapeutic practice.